Multiwavelength observations of a giant flare on CN Leonis: III. Temporal evolution of coronal properties - Liefke, Carolin; Fuhrmeister, Birgit; Schmitt, Jürgen (Astronomy and astrophysics, 2010)
Stellar flares affect all atmospheric layers from the photosphere over chromosphere and transition region up into the corona. Simultaneous observations in different spectral bands allow to obtain a comprehensive picture of the environmental conditions and the physical processes going on during different phases of the flare. We investigate the properties of the coronal plasma during a giant flare on the active M dwarf CN Leo observed simultaneously with the UVES spectrograph at the VLT and XMM-Newton.